Instructional Technology Practices in Developmental Education in Texas. Issue 1 (2nd January 2017) - Martirosyan, Nara M.; Kennon, J. Lindsey; Saxon, D. Patrick; Edmonson, Stacey L.; Skidmore, Susan T.
Abstract : The purpose of this study was to examine the current state of technology integration in developmental education in Texas higher education. Analyzing survey data from developmental education faculty members in 70 2- and 4-year colleges in Texas, researchers identified instructor-reported best instructional technology practices in developmental education and barriers impeding technology integration into developmental education instruction. Based on the findings, practical implications were drawn to supplement instructional and learning practices in developmental education courses.